Diversity of The Araceae Family in The Batutegi Protected Forest, Tanggamus, Lampung Based on Morphological and Molecular Characteristics - Yulianty; Ina Erlinawati; Nisha, Luthfiyyan; Wahyuningsih, Sri; Subagio, Aris (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Indonesia has a tropical climate bordering the equator, so it has a diverse biodiversity. Batutegi Protected Forest, Tanggamus is a lowland rainforest. Plants of tropical flora, including Araceae (taro), has a diversity level of 25% (31 genera) of plants found worldwide. Morphological and molecular characteristics can be used to analyze diversity. The aim of this study was to determine the diversity of Araceae plants based on morphological and molecular characteristics using DNA barcodes in the Batutegi Protected Forest area and the differences in marker genes matK, ITS and rbcL in determining the diversity of Araceae plants. The study was conducted in January-May 2023. Sampling was conducted in Batutegi Reserve Forest Tanggamus, Lampung using the exploration method. Morphological identification was performed through the herbarium collection in Herbarium Bogoriense, while molecular identification was performed using DNA barcoding with three marker genes including ribulose-1,5-bisphosphate carboxylase (rbcL), Maturase K (matK) and an internal transcribed spacer (ITS). Based on the studies conducted, it can be concluded that the Araceae plants found in the Batutegi Protected Forest, Tanggamus of Lampung have appropriate species results in terms of morphological and molecular characteristics. The matK marker gene performs better than ITS and rbcL with evidence of higher amplification success rates and a more informative phylogenetic tree.